Yin Yang 1 protein-activated N-acetyltransferase 10 drives cell malignant progression of osteosarcoma through ac4C acetylation of integrin β3 - Fan Yang; Mao Wang (Journal of Bone Oncology)
Background: N-acetyltransferase 10 (NAT10) acts as the “writer” of N4-acetylcytidine (ac4C) modification in tumor progression, including osteosarcoma (OS). Its molecular mechanism in OS remains not fully clear. This study endeavored to disclose the upstream and downstream mechanism of NAT10 related to Yin Yang 1 protein (YY1) and integrin β3 (ITGB3) in OS. Methods: Gene mRNA and protein levels were assayed via real-time quantitative PCR and Western blotting. Cell counting kit-8, EdU assay, flow cytometry/TUNEL staining assay, transwell assay, and scratch assay were conducted to assess cell viability, proliferation, apoptosis, invasion, and migration. Interaction analysis was completed through ac4C RNA immunoprecipitation (ac4c RIP), RIP, chromatin IP and dual-luciferase reporter assay. In vivo assay was carried out using xenograft models in mice. Results: OS tissues and cells showed the high expression of NAT10. Cell proliferation, invasion, and migration were suppressed but apoptosis was enhanced in NAT10-silenced OS cells. GSE237541 dataset has predicted the inhibition of ITGB3 after NAT10 knockdown, and PACES website predicted ac4C site in ITGB3. Furthermore, it was found that NAT10 could up-regulate ITGB3 expression by mediating ac4C acetylation. ITGB3 overexpression recused OS cell progression inhibition caused by NAT10 knockdown. Jaspar predicted the binding between YY1 and NAT10 promoter. YY1 could activate the transcriptional regulation of NAT10 to increase NAT10 expression, and YY1 depletion blocked cell malignant behaviors via reducing NAT10 expression. More importantly, YY1 interacted with NAT10 to up-regulate ITGB3 expression. In vivo, NAT10/ITGB3 axis also promoted OS tumor growth in mice. Conclusion: YY1 was firstly affirmed to regulate transcription of NAT10, and NAT10 was firstly indicated to mediate ac4C modification of ITGB3. YY1-activated NAT10 could affect ITGB3 and then modulated the malignant development of OS.